Anthropogenic and natural drivers of vegetation and fire history along the forest-steppe border of the eastern Andes (38-50°S) - Nanavati, William (2019)
Disentangling anthropogenic and natural drivers of vegetation and fire history at different spatiotemporal scales is a fundamental challenge in Earth Systems science. In the forest-steppe ecotone of southern South America, fire and climate have shaped the position of lower treeline, but the influence of pre-European peoples at the ecotone is less clear. A new 10,800-year history of climate, vegetation, fire, and land use from Laguna Portezuelo (38°S, 71°W, 1730 m elev.), east of the Andes, provides information on pre-European anthropogenic fires in Araucaria forest. Araucaria was an important resource for pre-Europeans and is ingrained into Mapuche-Pehuenche cultural identity. The pollen record shows that Araucaria expanded in the late Holocene with rising human populations and strengthened ENSO. Prior to that, the forest-steppe region supported scattered Nothofagus (mostly N. dombeyi-type pollen) and moderate-to-high fire activity. Beginning at 6800 cal yr BP, changes in ecotone composition and fire are attributed to increased climate variability and human presence. Increased Nothofagus and Araucaria pollen and null-to-low fire activity occurred at 1800, 1200, and 800 cal yr BP, in association with increased strength and frequency of wet El Niño events. After 500 cal yr BP, increased abundance of Plantago, Rumex, and other disturbance taxa (e.g., Apiaceae and Caryophyllaceae) and high fire activity mark Euro-American land use. Non-native Pinus pollen in the 20th century indicate the establishment of Pinus plantations near Laguna Portezuelo.Although archaeological investigations suggest that people lived in southern South America east of the Andes since ca. 12,000 cal yr BP, the vegetation and fire history for most of the postglacial period was governed by the strength and position of the SWW storm tracks. From the late-glacial to early Holocene, region-wide increases in fire were associated with aridity while the SWW were weakened and south of their present position. Between 7000-4000 cal yr BP, increased arboreal taxa and decreased fire throughout Patagonia suggest effectively wet conditions, as the SWW moved northward to their present position. After 4000 cal yr BP, a combination of rising human population and greater climate variability, led to spatially heterogeneous but generally rising fire activity along the forest-steppe ecotone. Throughout Patagonia, wet El Niño and/or negative Southern Annual Mode (SAM) events increased biomass, but made the landscape less flammable and reduced anthropogenic burning. Transitions from wet El Niño and/or negative SAM to dry La Niña and/or positive SAM events increased burnable biomass, amplifying anthropogenic burning. During the last 100 years, increased Euro-American settlement and land clearance led to forest loss, more disturbance, and the spread of introduced taxa along the eastern flanks of the Andes. The ecological changes in recent decades far outweigh thousands of years of pre-European human influence on fire and vegetation history.